Analysis of Consumer Purchase Decisions in Tangerang Old Market with Consumer Satisfaction as an Intervening Factor - Diana Silaswara; Agus Kusnawan; Eso Hermawan (LPPM Universitas Buddhi Dharma, 2024)
The old market is a historical place in the Tangerang City area which is very related to trade activities in the city of Banten during the colonial era. Trade activities in this area have been running since ancient times where this area is a residential area or village whose residents have indeed become traders and carry out trading activities. The development of the old market that lasted for several decades is the reason for this research. This study is to find out what factors in the marketing mix satisfy consumers so that they finally decide to make the desired culinary purchase at Tangerang Old Market. With causal research and using the PLS (Partial Least Squares) analysis method, we can find out how strong the relationship is formed between each latent variable and the indicators in it and find out how much satisfaction is generated by the marketing mix factor so as to strengthen consumer purchase decisions. Based on data from 100 valid questionnaires obtained, it is known that the latent variables studied have been represented by their indicators and these variables are reliable. And it turns out that the factors of the marketing mix contribute 24.9% to the purchase decision with the dominant factors that provide satisfaction to consumers are the product factor and the price factor with values of 2.907 and 2.740 (t table = 0.67711), while other factors such as place and promotion are not too influential (values 0.562 and 0.525).